Case report: Distinctive cardiac features and phenotypic characteristics of Noonan syndrome with multiple lentigines among three generations in one family - Chan, Chon-Hou; Chu, Man-Fong; Lam, U-Po; Mok, Toi-Meng; Tam, Weng-Chio; Tomlinson, Brian; Coelho, Ricardo; Évora, Màrio (Frontiers in Cardiovascular Medicine, 2023)
Noonan syndrome with multiple lentigines (NSML, formerly known as LEOPARD syndrome) is a variant of Noonan syndrome which is an autosomal dominant disorder. Most cases of NSML are secondary to mutations of the protein-tyrosine phosphatase nonreceptor type 11 (PTPN11). Hypertrophic cardiomyopathy (HCM) remains the most frequent and serious cardiac abnormality in this inherited syndrome, and it may lead to sudden cardiac death related to HCM-associated outflow obstruction and fatal arrhythmia. Beyond cardiac involvement, NSML may present with multiple lentigines, ocular hypertelorism, genital anomalies, short stature and deafness. Herein, we report three patients with NSML among three generations in one family, all presenting with multiple lentigines, HCM and other distinctive clinical and molecular features, including facial dysmorphism, deafness, family history of sudden death and PTPN11 mutations. This case series highlights the importance of early echocardiography examinations for patients with NSML. Careful family screening and genetic counselling are also necessary, especially in patients with diffuse lentigines or a history of sudden death among family members. We also discuss the distinctive cardiac features and phenotypic characteristics at different stages of NSML, including childhood, adulthood and elderhood.